The role of the Riau Regional Police Forensic Laboratory in the 2024 Fire Case Disclosure Strategy in Riau Province - lisastri, dhevi; Rio Tutrianto (Sisi Lain Realita, 2026)
This research aims to analyze the role of the Riau Regional Police Forensic Laboratory in the strategy of disclosing fire cases in Riau Province in 2024. The increasing phenomenon of fires, both in the residential sector, public facilities, and forest and land fires (karhutla), demands a scientific approach in the process of investigation and legal proof. This research uses descriptive qualitative methods with data collection techniques through in-depth interviews, observations, and documentation. The research results show that the Riau Regional Police Forensic Laboratory has a strategic role in determining the cause of the fire through scientific analysis such as identification of the starting point of the fire (point of origin), analysis of the spread of the fire, and the detection of accelerated materials using technologies such as Gas Chromatography–Mass Spectrometry (GC-MS). In addition, the results of laboratory examination become an important evidence in the investigation and trial process. However, in its implementation there are obstacles such as limited human resources, delayed access to the scene, and lack of supporting facilities in several regions. Therefore, it is necessary to strengthen institutional capacity, improve HR competence, and optimise inter-agency coordination to increase the effectiveness of fire case disclosure scientifically and accountable.